The Influence of Intellectual Intelligence and Emotional Intelligence on Work Ethic and Its Impact on Performance - Agustina, Fransiska (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Kartini Maternal and Child Hospital is one of the specialized hospitals in West Bandung, focusing on maternal and child healthcare services. In addition, it is one of the few private hospitals in West Bandung that has received accreditation, although it is still at the basic level. This condition has motivated the hospital to strive toward achieving excellent service and attaining the highest level of accreditation (paripurna), with the ultimate goal of becoming a leading hospital in the region. This motivation led the author to investigate issues related to the performance of nurses at this hospital, particularly in terms of their intellectual intelligence, emotional intelligence, work ethic, and job performance. The aim of this study is to examine the influence of intellectual intelligence and emotional intelligence on work ethic, as well as the influence of work ethic on nurses' performance. The study involved a total of 45 respondents, selected using the saturated sampling technique. This research is categorized as descriptive and verificative. The methods of analysis employed in this study include correlation coefficient analysis, validity testing, and reliability testing. Based on the results of the analysis, all research hypotheses were accepted, indicating that all proposed variables — intellectual intelligence and emotional intelligence — have a significant influence on work ethic, and that work ethic contributes positively to nurse performance.